Pure narco: one man's true story of 25 years inside the cartels - Fink, Jesse (Rowman & Littlefield, 2021)
"Pure Narco tells the tale of arguably America's biggest cocaine trafficker and his capture in Venezuela during one of the biggest anti-narcotics takedowns of all time. But it is more than that; Pure Narco is unique in that it is a story of a family caught up in a life on the run and Luis Navia's adjustment to civilian life after prison"--